The Correlation Between Lifestyle And The Incidence Of Gastritis Among Adolescents In Jimbar Village At Pracimantoro Wonogiri - Rika (Journal of health research and technology, 2026)
Abtract Introduction: Gastritis is a common condition in the community, particularly among adolescents. It arises from inflammation of the gastric mucosa caused by irritation and infection resulting from continuous mechanical stress, leading to abrasions and lesions. Adolescents falling within the productive age range of 1525 years are known to be susceptible to gastritis. This age group is particularly vulnerable to gastritis symptoms due to high levels of physical activity, busy schedules, stress, and poor lifestyle choices, all of which can negatively impact dietary patterns, meal frequency, and nutritional intake. This study aims to determine the correlation between lifestyle and the incidence of gastritis among adolescents in Jimbar Village at Pracimantoro Wonogiri. Methods: This study employed a descriptive-correlational design with a crosssectional approach. Proportional random sampling was used to select a sample of 142 adolescents from Jimbar Village, Pracimantoro, Wonogiri. Data analysis was conducted using the Gamma statistical test, and the research instruments consisted of two questionnaires administered via Google Forms: a 38 item lifestyle questionnaire and a 9 item questionnaire regarding the incidence of gastritis. Results: The study results indicate that the majority of adolescents in Jimbar Village fell into the moderate category for lifestyle. In contrast, the incidence of gastritis among them fell into the moderate category. The Gamma statistical test yielded a p-value of 0.0001 (< 0.05), indicating a significant correlation between lifestyle and the incidence of gastritis among adolescents in Jimbar Village at Pracimantoro Wonogiri. Conclusion: The study concludes that there is a correlation between lifestyle and the incidence of gastritis among adolescents in Jimbar Village at Pracimantoro Wonogiri. Keywords : Lifestyle, Gastritis, Adolescents Corresponding author(s): Rika Saputri1, Fakultas Sains Teknologi dan Kesehatan, Universitas Sahid Surakarta, Jl. Adi Sucipto No.154 Jajar, Laweyan, Surakarta, Jawa Tengah, Indonesia, Kode pos 57144, Email: rikasaputriii20@gmail.com